2021
DOI: 10.1038/s42003-021-01775-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced NRT1.1/NPF6.3 expression in shoots improves growth under nitrogen deficiency stress in Arabidopsis

Abstract: Identification of genes and their alleles capable of improving plant growth under low nitrogen (N) conditions is key for developing sustainable agriculture. Here, we show that a genome-wide association study using Arabidopsis thaliana accessions suggested an association between different magnitudes of N deficiency responses and diversity in NRT1.1/NPF6.3 that encodes a dual-affinity nitrate transporter involved in nitrate uptake by roots. Various analyses using accessions exhibiting reduced N deficiency respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 72 publications
0
27
0
Order By: Relevance
“…The selected member of NRT/PTR family was commonly downregulated in all conditions. Transporters of NRT1/PTR family function as low-affinity transporters (Sakuraba et al, 2021) and show down-regulation in response to N deficiency in plants (Islam, 2019;Lejay et al, 1999) and P starvation in barley (Long et al, 2019). The transcript levels of these three genes obtained by qRT-PCR were consistent with the patterns apparent in the RNAseq analysis; PHT1.1 and PHT1.13 were upregulated in LP, while NRT/PTR family 6.1 showed significant reduction in transcript levels in LN and LNP (Supplemental Figure S1A).…”
Section: Rna Sequencing Data Analysis and Identification Of Different...mentioning
confidence: 99%
“…The selected member of NRT/PTR family was commonly downregulated in all conditions. Transporters of NRT1/PTR family function as low-affinity transporters (Sakuraba et al, 2021) and show down-regulation in response to N deficiency in plants (Islam, 2019;Lejay et al, 1999) and P starvation in barley (Long et al, 2019). The transcript levels of these three genes obtained by qRT-PCR were consistent with the patterns apparent in the RNAseq analysis; PHT1.1 and PHT1.13 were upregulated in LP, while NRT/PTR family 6.1 showed significant reduction in transcript levels in LN and LNP (Supplemental Figure S1A).…”
Section: Rna Sequencing Data Analysis and Identification Of Different...mentioning
confidence: 99%
“…It can be seen that MeNPF4.5 responds to NO 3 – in the short term like many other plants NRT1.1 ( Cárdenas Navarro et al, 1998 ; Okamoto et al, 2003 ; Wang et al, 2007 ). In addition to being expressed in roots, AtNRT1.1 is also expressed in shoots, young leaves, and developing flower buds of Arabidopsis , but it is more strongly expressed in roots ( Miller et al, 2007 ; Sakuraba et al, 2021 ). Consistent with the expression pattern of NRT1.1 in Arabidopsis , MeNPF4.5 is expressed in roots, stems, and leaves of cassava plants, and it is predominantly expressed in roots.…”
Section: Discussionmentioning
confidence: 99%
“…At present, NRT/NPF genes have mainly been identified in A. thaliana and rice, and their functions and regulatory mechanisms have been studied in detail ( Liu et al, 2015 ; Sakuraba et al, 2021 ). For example, studies have shown that rice NRT1.1B is located in the cell membrane and plays an important role in the transport of NO 3 – from the adventitious roots to the leaves ( Hu et al, 2015 ; Zhao et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among the NRT1/PTR family proteins, NRT1.1 is considered as a unique protein, since it acts as a dual affinity transporter that can facilitate nitrate uptake at concentrations ranging from micromolar to millimolar (Liu et al, 1999). Genome-wide association study (GWAS) of Arabidopsis accessions suggested a significant association between differences in N starvation-induced leaf yellowing and NRT1.1 sequence diversity (Sakuraba et al, 2021b). Indeed, nrt1.1 knockout mutant, chl1-5 exhibited accelerated leaf yellowing, while transgenic NRT1.1-overexpressing (NRT1.1-OX) plants retained greenness under N-deficient conditions (Sakuraba et al, 2021b).…”
Section: Roles Of Nitrate Transporters In N Remobilizationmentioning
confidence: 99%
“…In addition, leaf yellowing due to the remobilization of N sources from older leaves to younger leaves and reproductive organs is also one of the representative N deficiency responses and is considerably important for plants to sustain growth and productivity. On the other hand, N starvation-induced leaf yellowing in young seedlings causes severe growth defects (Sakuraba et al, 2021b). Therefore, understanding the molecular mechanisms underlying N starvation-induced leaf senescence is critical for establishing sustainable agriculture under N-deficient conditions.…”
Section: Introductionmentioning
confidence: 99%